Socio-economic status, self-rated health and mental health: the mediation effect of social participation on early-late midlife and older adults - Netta Achdut; Orly Sarid (BMC, 2020)
Abstract Background Socioeconomic status (SES) is a major determinant of diverse health outcomes, among these are self-rated-health and mental health. Yet the mechanisms underlying the SES-health relation are not fully explored. Socioeconomic inequalities in health and mental health may form along several pathways. One is social participation which is linked to better self-rated-health and mental health. We examined (1) whether various social participation practices, including the usage of information and communication technology, relate to a unidimensional or multidimensional phenomenon (2) the relationship among SES, social participation, self-rated-health and mental health; (3) whether social participation and mental health mediates the association between SES and self-rated-health; (4) whether social participation and self-rated-health mediates the links between SES and mental health. Method Cross-sectional data for individuals aged 35 and older were taken from the Israeli Social Survey for 2016 (N = 4848). Social participation practices included connection with family and friends, self-perceived-support, self-perceived trust, volunteering, civic and political involvement, and information and communication technology usage. An exploratory factor analysis was conducted for all social participation practices. We then constructed structural Equation Modeling (SEM) to explore paths of relations among SES, social participation, self-rated-health and mental health. Results We found disparities in self-rated health and mental health across SES. Social participation practice, 'frequency of meeting with friends', mediated the links between SES-self-rated health and SES-mental health. Formal social participation practices along with internet usage mediated the SES- self-rated health link. Informal social participation practices and self-perceived trust mediated the SES-mental health link. Mental health mediated the SES- self-rated health link and self-rated health mediated the SES-mental health link. Conclusion The links between SES and the two health constructs were enhanced by common and distinct social participation practices. Enhancement of social participation practices among low SES individuals is recommended. Social participation should be a prominent aspect of preventive medicine practice and health promotion interventions. Policy makers are called to support such programs as an important way to promote public health.